Efektivitas Massage Payudara dengan Teknik “Z” Terhadap Produksi ASI Ibu Nifas - Ana Rofika (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Introduction: A decrease in breast milk production in the first days after giving birth can be caused by a lack of stimulation of the hormones oxytocin and prolactin which play a very important role in the smooth flow of breast milk, causing breast milk not to come out immediately after delivery and the baby having difficulty sucking on the mother's nipple. Currently, in midwifery services, complementary-based services have emerged, which often include breast massage to overcome irregularities in breast milk production. Breast massage is the act of gently massaging the breasts which can be done every day. Method: This study aims to determine the effectiveness of breast massage using the